LO024: Time to perform ultrasound guided femoral nerve block in older hip fractures patients by emergency physicians. (2nd June 2016) - Lee, J.S.; Bhandari, T.; Simard, R.; Kiss, A.; Chenkin, J.
Abstract : Introduction: Ultrasound-guided femoral nerve block (USFNB) is optimal for providing analgesia for patients with hip fractures, but is rarely performed. Time of the procedure was cited as a barrier in our previous survey.Methods: We conducted a knowledge-to-practice intervention that included a two-hour training session on USFNB, use of a block kit, and reminders to improve uptake of USFNB. We measured the time it took for trained EPs to complete the block during a 20 month period.Results: Of 36 EPs, 34 (94.4%) were not routinely performing USFNB at the beginning of the study, and 4 declined to participate, leaving 30 participants who received training. The 30 trained EPs performed 100 USFNB over the next 20 months (range 1 to 20 blocks per EP). The mean reduction in pain was -4.47 on a 10 point numeric rating scale. The median time to perform the blocks was 15.0 minutes (IQR, 10 to 20 minutes), and 90 % of blocks took less than 30 minutes. The most common reason given for not performing a block was excessive clinical load.Conclusion: Given that we included 88.2% of eligible EP's and included the first time EP's performed a USFNB, our estimates of time to perform USFNB block should generalize to other Canadian academic ED's. Time to complete USFNB is in keeping with other commonly performed ED procedures and should not be a barrier to optimizing analgesia.